Fundamentals and applications of self-assembled plasmonic nanoparticles at interfaces. (25th January 2016) - Edel, Joshua B.; Kornyshev, Alexei A.; Kucernak, Anthony R.; Urbakh, Michael
Abstract : This tutorial review covers applications and fundamentals of self-assembled plasmonic nanoparticles at liquid|liquid and liquid|air interfaces. Abstract : This tutorial review will introduce and explore fundamental and applied aspects of electrolytic interfaces incorporating nanoscale building blocks for use in novel applications such as sensors and tunable optics. In order to do this, it is important to understand the principles behind even the simplest of immiscible interfaces such as those of the liquid|liquid and solid|liquid. Qualitatively, the picture is simple however the complexity is easily compounded by the addition of electrolyte, and further compounded by the addition of more complex entities such as nanoparticles. Nevertheless combining all these components surprisingly results in an elegant solution, where the nanoparticles have the ability to self-assemble at the interface with a high level of control. Importantly, this opens up the door to the development of new types of materials with a range of applications which have only recently been exploited. Initially we begin with a description of the fundamentals related to liquid|liquid and solid|liquid interfaces both with and without electrolyte. The discussion then shifts to a description of biasing the interface by the application of an electric field. This is followed by an exploration of nanoparticle assembly and disassembly at the interface by controlling parameters such as ligand composition, charge, pH, and electric field. Finally a description of the state-of-the-art is given in terms of current applications and possible future directions. It is perhaps fair to say that these new frontiers have caused great excitement within the sensing community not only due to the simplicity of the technique but also due to the unprecedented levels of sensitivity and control.